Comparative analysis of the philosophy of space and time in the Kazakh falsafe with the philosophical traditions of other peoples (Journal of Philosophy Culture and Political Science, 2024)
The philosophy of space and time represents an important direction in philosophical research, enriching the understanding of the nature of time and space in the context of the cultural, historical, and philosophical traditions of various peoples. This article conducts a comparative analysis of the philosophy of space and time in the Kazakh philosophical tradition with the philosophical traditions of other nations, such as Chinese and Greek.The article emphasizes the relevance of studying this topic in the modern world, where rapid technological progress, climate change, globalization, and cultural diversity present us with new challenges and changes. The philosophy of space and time contributes to a deep understanding of the impact of these changes on our perception of the world.The analysis of the philosophical views of Kazakh philosophy, based on nomadic culture, Islam, and historical factors, reveals the unique features of this philosophical tradition. A comparison with Chinese and Greek philosophy highlights similarities and differences in the understanding of time and space, enriching the philosophical dialogue between cultures.Furthermore, the analysis of the influence of cultural and historical factors on the formation of the philosophy of space and time in Kazakhstan underscores the importance of these factors in shaping philosophical traditions.Thus, this article calls for the continued study of the philosophy of space and time in the modern world to better understand the challenges and changes we face and to develop deeper and more balanced approaches to addressing them.        Key words: time, space, cultural factors, Kazakh falsehood, philosophical traditions.